(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This paper explores the historical roots of English idioms and phrases that incorporate bird names (ornithonyms). It examines how cultural perceptions, folklore, and practical observations of avian behavior have shaped the meanings and usage of these expressions over time. By tracing the etymology of selected ornithonym-based idioms, this study aims to shed light on the evolving relationship between language, culture, and the natural world.